PENGARUH LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS YANG DIMODERASI OLEH GOOD CORPORATE GOVERNANCE (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018) - Putri Meidiana Shavira; halim herman Edyanus; Fitri fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study was aims to examine the effect of Loan to Deposit Ratio, Non Performing Loan and Operating Cost of Operating Income on Profitability with Good Corporate Governance as a moderating variable. Loan to Deposit Ratio, Non Performing Loan and Operating Cost of Operating Income are measured by using the published companies annual report, and the company's Profitability is measured by using ROA. The research method used in this research was quantitative method that aimed to examine Good Corporate Governance in moderating the effect of Loan to Deposit Ratio, Non Performing Loan and Operating Cost of Operating Income on Profitability. This research used 29 banking companies as the sample. The sample was chosen used purposive sampling that the companies must be listed in Indonesia Stock Exchange, and publishing a complete annual report and GCG report during period 2014-2018. To analysis the data, this research used Moderated Regression Analysis by using Statistical Package for the Social Sciences (SPSS). The results of this study indicate that, Loan to Deposit Ratio and Operating Cost of Operating Income have a significant yet negative effect on Profitability. while Non Performing Loan have a non significant and negative effect on profitability. Loan to Deposit Ratio, Non Performing Loan and Operating Cost of Operating Income that moderated by Good Corporate Governance have a significant and positive effect on Profitability.Keywords : Loan to Deposit Ratio, Non Performing Loan, Operating Cost of Operating Income, Good Corporate Governance, Profitability.